O diagnóstico tardio e óbito por aids de pacientes internados em 2005 em um hospital de referência para doenças infecciosas em Belo Horizonte, Minas Gerais. - Maria Tereza da Costa Oliveira (2007)
Introduction: The highly active antiretroviral therapy (HAART) has substantially changed the prognostic of aids patients worldwide. In that sense, Brazil has obtained relevant results due to the assistance given in the country to every person living with HIV/AIDS. However, many patients do not get to benefit from these resources because they have the HIV diagnosis made late. Methodology: This study follows a cohort of AIDS patients, who are hospitalized for the first time during the year of 2005 in Eduardo de Menezes Hospital, with information about their HIV diagnosis date. This hospital is located in the city of Belo Horizonte, State of Minas Gerais, and is the biggest AIDS attending complex in the state. It hasmore than 500 AIDS hospitalizations annually, which represents 25% of these hospitalizations in the whole State. The patients are followed since their first hospitalization in 2005 until 31st December 2006. The deaths which took place in the period and its associated factors are verified, as well as the use of HIV/AIDS treatment services and the occurrenceof late diagnosis. The accumulated survival probability after 12 months from the first hospitalization to treat AIDS and the prognostic factors are estimated. Results and discussion: 250 patients are followed up. A total of 99 people (39.4%) died during the follow-up period, from these 75 (75.8%) died during the first hospitalization. Almost half the patients (44.8%) had their HIV diagnosis made in less than a month before their hospitalization to treat AIDS. Most of the patients (60.0%) were not being followed by a HIV/AIDS treatment service prior to their hospitalization. The time frame between the HIV diagnosis and the death is up to three months in more than half of the cases (53.5%) and about 1 4 of the patients died in less than a month after being diagnosed. Two different multivariate logistic regression models are adjusted to find the factors associated to death due to AIDS. The associated factors found in the model 1 are: being a male and living in the countryside (OR=4.15 CI95%1.49; 11.56) and not having any registration of CD4+ cell count (OR=6.95 CI95%=3.25; 14.86). In the second model they are: being a male and living in the countryside (OR=3.87 CI95%=1.46; 10.22); not having used ARV (OR=3.24 CI95%=1.01; 10.44), in case of its previous use, not during hospitalization (OR=3.23 CI95% 1.10; 9.48); and presenting severeanemia at the time of hospitalization (OR=4.16 CI95%=1.34; 12.92). The accumulated survival probability after 12 months from the first hospitalization in this group is estimated in 61.2%. However, patients diagnosed during hospitalization have a survival median of four months. This survival median is inferior to that one estimated to AIDS patients before HAART was introduced. The multivariate hazard ratio models verify the same factors of the multivariate logistic regression models as prognostic of death due to AIDS. Conclusions and recommendations: In sum, the data of this work done in Eduardo de Menezes hospital in Belo Horizonte confirms the occurrence of late diagnosis of HIV infection andits association with a high mortality due to AIDS. Health professionals and managers, as well as the population, must be informed of late HIV diagnosis and its consequences. It is essential to facilitate HIV infection diagnosis, with the appropriate counseling, and increase access to health services so these can actually reach the population in need.